Pengaruh Capital Adequacy Ratio (CAR), Return On Assets (ROA) dan Non Performing Financing (NPF) Terhadap Pembiayaan Murabahah BNI Syariah - Amirah Ahmad Nahrawi (Perisai : Islamic Banking and Finance Journal, 2017)
There are hundreds of Islamic banks registered in Indonesia, which means Islamic banks have a huge contribution in the economic performance of the country. According to Islamic bank statistic's data, the most prefered transaction is murabahah financing, which reached 57,76 %. To understand this trend, one should first relate to the affecting factors, such as Capital Adequacy Ratio (CAR), Return on Asset (ROA) and Non Performing Financing (NPF). Therefore this research aims to find out the influence (Partial & simultant) of the factors mentioned above on the Murabahah financing in BNI Syariah for the period of 2011 - 2015.Using quantitative and descriptive approach, this research present and analyise published data obtained from BNI's financial report 2011 to 2015 as sample, and other references as based theory. All data analysed using Statistical Program for Social Science (SPSS). While for assuring data accuracy, normality test, autocorelation and heterostatistics tests have been made. The relation and the influence between dependent and independent variables, figured by double regression analysis. Based on the partial analysis each variables showed have positive and significant effect on murabahah financing. Through the Double Reggression conducted, it found that the variables CAR, ROA and NPF together have positive and significant effect on murabahah financing.In conclusion, to maintain the murabahah financing level, the bank should maintain and improve CAR, ROA, and NPF.